Occupational asthma: management beyond the textbooks - Cullinan, Paul (Henry Stewart Talks, 2012)
A wide variety of agents can cause occupational asthma, A case study of possible occupational asthma, Important points to consider for potential occupational asthma sufferers; diagnosis and approach, Identification and care of patients